Large-scale functionalization of biomedical porous titanium scaffolds surface with TiO2 nanostructures - Qian, Lei; Yu, Peng; Zeng, Jinquan; Shi, Zhifeng; Wang, Qiyou; Tan, Guoxin; Ning, Chengyun (Science China materials, 2018)
Construction of functional porous titanium scaffold is drawing ever growing attention, due to its effectiveness in solving the mechanical mismatch between titanium implant and bone tissue. However, the poor water permeability as well as the problem in achieving uniform surface modification inside scaffold hinders the further biomedical application of porous titanium scaffold. In this study, largescale functional TiO 2 nanostructures (nanonetwork, nanoplate and nanowire) were constructed on three-dimensional porous titanium scaffolds surface via an effective hydrothermal treatment method. These nanostructures increase the hydrophilicity of the titanium scaffold surface, facilitating the cell culture medium to penetrate into the inner pore of the scaffold. Zeta potential analyses indicate that the surface electrical properties depend on the nanostructure, with nanowire exhibiting the lowest potential at pH 7.4. The influence of the nano-functionalized scaffold on protein adsorption and cell adhesion was examined. The results indicate that the nano-functionalized surface could modulate protein adsorption and bone marrow derived mesenchymal stem cells (BMSCs) adhesion, with the nanowire functionalized porous scaffold homogeneously promoting protein adsorption and BMSCs adhesion. Our research will facilitate future research on the development of novel functional porous scaffold.